Protein aggregates and biomolecular condensates: implications for human health and disease - Navalkar, Ambuja; Arunagiri, Anoop; Kee, Tovaria; Panchal, Kathigna; Dick, Kathryn (Frontiers in Molecular Biosciences, 2025)
Biomolecular condensates are at the forefront of understanding biological concepts, representing one of the most revolutionary areas in cell biology over the last decade. Numerous proteins, peptides, and nucleic acids have been shown to form membrane-less organelles, also known as condensates, in cells, demonstrating their functional relevance. Multiple research approaches in the fields of physics, chemistry, and biophysics investigate the underlying multivalent interactions that influence the phase separation of biomolecules. As failure to regulate condensate properties, such as formation and/or dissolution has been postulated as a driver of the misfolding and aggregation of proteins in stress, aging, and neurodegeneration disorders, understanding the fundamentals of condensate assembly has been considered of utmost importance. In this review, we will focus on the key regulators and biophysical drivers of phase separation and protein aggregation, evidenced in the literature. We will elaborate on the dynamic interplay between phase separated and aggregated state, highlighting the emergent properties of condensates that can contribute to the misfolding of proteins in the context of physiology and diseases. An in-depth understanding of condensate pathology can reveal novel avenues for targeting proteinopathies linked to misfolding.